2019
DOI: 10.1038/s41598-019-41434-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Genome-Wide Association Studies of eQTL and GWAS Data for Gout Disease Susceptibility

Abstract: There is a paucity of genome-wide association study on Han Chinese gout patients. We performed a genome-wide association meta-analysis on two Taiwanese cohorts consisting of 758 gout cases and 14166 controls of Han Chinese ancestry. All the participants were recruited from the Taiwan Biobank. For pathway analysis, we applied ICSNPathway (Identify candidate Causal SNPs and Pathways) analysis, and to investigate whether expression-associated genetic variants contribute to gout susceptibility, we systematically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…Furthermore, only based on the findings of GWAS analysis is impossible to infer whether the detected disease-associated SNPs contain regulatory functions. Thus, Sherlock integrative analysis is a good and effective method for combining the information of GWAS with eQTL data and has been applied to identify many novel risk genes of many complex diseases [15,[19][20][21][22], which cannot be detected by GWAS alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, only based on the findings of GWAS analysis is impossible to infer whether the detected disease-associated SNPs contain regulatory functions. Thus, Sherlock integrative analysis is a good and effective method for combining the information of GWAS with eQTL data and has been applied to identify many novel risk genes of many complex diseases [15,[19][20][21][22], which cannot be detected by GWAS alone.…”
Section: Discussionmentioning
confidence: 99%
“…He et al [15] introduced a Bayesian statistical approach of Sherlock to systematically reveal the cis-and trans-regulatory effects of risk genes on complex diseases based on GWAS summary data and eQTL data. By using this bioinformatics tool, numerous studies have identified many novel risk genes, which cannot be found with the use of the GWAS approach alone, for different complex traits, such as schizophrenia [19], gout disease [20], and major depressive disorders [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Allopurinol indeed has the corresponding action in Drosophila; addition to the diet increases xanthine and hypoxanthine, and decreases urate and allantoin (Al Bratty et al 2011). A number of quantitative trait loci associated with gout have been identified in humans (Cheng et al 2004;Li et al 2007;Cummings et al 2010;Matsuo et al 2011;Lee et al 2019), and it will also be interesting to see whether Drosophila orthologs of these genes also play a role in maintaining fly urate levels.…”
Section: Modeling Disease Processesmentioning
confidence: 99%
“…Comparison of typical GWAS approach that generally abandon a large number of common genetic variants with moderate-to-small effects, Sherlock analysis is an effective and powerful tool for utilizing these abandoned common variants in GWAS. By using this tool, many novel risk genes, which are difficult to be identified by any single typical GWAS, were prioritized to involve in the pathogenesis of numerous complex diseases, including schizophrenia [ 31 ], major depressive disorders [ 32 , 33 ], and gout disease [ 34 ].…”
Section: Introductionmentioning
confidence: 99%